1994
DOI: 10.1177/096368979400300110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FK506 and Anti-CD4 Therapy on Fetal Pig Pancreas Xenografts and Host Lymphoid Cells in NOD/Lt, CBA, and BALB/c Mice

Abstract: Varying doses of FK506, and a cell-depleting anti-CD4 monoclonal antibody, GK1.5, were tested as either monotherapy or in combination for their effect on the survival of renal subcapsular xenografts of organ-cultured fetal pig pancreas in three strains of mice. Subcutaneous injections of FK506 at 4.0 mg/kg/day for 28 d prevented graft rejection to day 35 posttransplantation (i.e., 7 days after cessation of treatment in NOD/Lt, and CBA mice) while BALB/c mice had intact grafts at 28 days. Lower doses were less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…FK506 is a relatively new immunosuppressive agent that is now undergoing extensive clinical trials, however, its effect on xenografts has been less well studied. Mandel et al reported that Fl<506 at 4 mg/kg/day significantly prolonged the survival of fetal pig pancreas xenograft in 3 strains of mice (18). Earlier, we observed prolonged histological survival of human islets in xenogenic rat recipients treated with FK506 (19).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…FK506 is a relatively new immunosuppressive agent that is now undergoing extensive clinical trials, however, its effect on xenografts has been less well studied. Mandel et al reported that Fl<506 at 4 mg/kg/day significantly prolonged the survival of fetal pig pancreas xenograft in 3 strains of mice (18). Earlier, we observed prolonged histological survival of human islets in xenogenic rat recipients treated with FK506 (19).…”
Section: Discussionsupporting
confidence: 52%
“…Earlier, we also reported the prolongation of human islets in rats for up to 2 months of xenograft under the kidney capsule (19). In the pig to mouse xenograft studies, hyperacute rejection was also present (18). It is apparent that, if hyperacute rejection of xenografts due to preformed natural antibody can be avoided, the major attack on the transplant is T-cell mediated (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Long-term human, bovine and porcine islet xenograft survival has been documented in nude mice and rats, suggesting that sufficient islet-specific growth factors are present in xenogeneic recipients. [12][13][14][15][16][17] Adult porcine islets are difficult to isolate and to maintain in vitro; nevertheless, they are extremely promising for eventual clinical application since their glucose-responsiveness is similar to that of humans. 9,10 Isolation of bovine islets is technically easier (than porcine islets), and calf islets are glucose-responsive; 10 however, adult bovine islets are relatively insensitive to glucose.…”
Section: The Rationale For Microencapsulated Islet Xenograftsmentioning
confidence: 99%
“…9–11 Long‐term human, bovine and porcine islet xenograft survival has been documented in nude mice and rats, suggesting that sufficient islet‐specific growth factors are present in xenogeneic recipients. 12–17…”
Section: Introductionmentioning
confidence: 99%